Treatment strategy of unstable atlas fracture: A retrospective study of 21 patients. Issue 18 (May 2020) - Guo, Wei; Lin, Yang; Huang, Jingwen; Hu, Feng; Ding, Zhou; Xiao, Zengming
Abstract : Abstract: At present, the posterior cervical approach with open reduction and internal fixation (ORIF) remains a commonly effective treatment for unstable Atlas fracture. However, the inserted screws into the C1 lateral mass of some unstable atlas fracture are very difficult, so that the operation is forced to change into C0 to C2 fusion. In order to improve the successful rate of lateral mass screw placement, we introduced a method of fixing lateral mass with a towel clamp in posterior transpedicular fixation, and explore the efficacy and feasibility. Twenty-one consecutive patients with unstable atlas fracture were treated via this method from October 2012 to July 2017. All cases had neck pain and restricted motion of neck movement on admission. Electronic medical records and pre- and postoperative radiographs were reviewed. Screw and rod placement, bone fusion, and spinal cord integrity were assessed via long-term follow-up with anteroposterior and lateral radiographs and computed tomography. Follow-up included clinical assessment of neurological function, assessment of pain using the visual analog scale (VAS), and assessment of the activities of daily living using the neck disability index (NDI). The mean follow-up duration was 22.1 months (range: 12–54 months). No screw loosening or breakage, plate displacement, neurovascular injury, and severe complications occurred during follow-up. The mean operative time was 112.4 ± 14.9 min (range: 82–135 min), and mean blood loss was 386.2 ± 147.9 mL (range: 210–850 mL). One patient experienced continuous neck pain postoperatively, but this gradually disappeared with analgesic administration. At final follow-up, all patients had bone fusion, the VAS scores and NDI were significantly improved compared with preoperatively. Fixing the C1 lateral mass with a towel clamp during posterior transpedicular fixation for unstable atlas fracture appears to be a safe and reliable method, with the advantages of being a simple technique with few complications.